Transplantation Techniques of Pocillopora verrucosa and Stylophora pistillata (Anthozoa) Single and Mixed Systems in the Planting Area of Bali, Indonesia for Coral Reef Conservation - Lady Ayu Sriwijayanti; Djumanto; Namastra Probosunu (Geography, Earth Science and Environment: Research Highlights Vol. 3, 2025)
The area of world coral reefs is decreasing, and the percentage of cover is getting lower, which requires immediate remedial action through transplantation and several other methods. This study aims to compare the transplantation techniques of Stylophora pistillata and Pocillopora verrucosa single and mixed systems carried out on the coast of Serangan Bali, Indonesia. Clumps of S. pistillata and P. verrucosa obtained from cultivation (F1) were cut using pliers and transplanted into a substrate made of a mixture of cement and sand; then, both species were cultivated in single and mixed structures. Growth observations and environmental data were collected weekly from October 2016 to January 2017. The growth data recorded were vertical growth, colony diameter, number of new polyps, and ecological parameters of temperature, pH, salinity, and current. Growth performance was evaluated by t-test with a confidence level of <5%. The results showed that during 12 weeks of cultivation, S. pistillata significantly showed faster vertical growth, wider colony diameter, and more polyps than P. verrucosa. Furthermore, coral transplantation in single species had substantially better growth performance than mixed cultivation, and the survival rate reached 100%. Transplantation of S. pistillata and P. verrucosa, corals in a single system, can be recommended as a coral reef conservation strategy in damaged coral ecosystems.